2014
DOI: 10.3892/mmr.2014.1919
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 gene expression in oral lichen planus: A clinicopathological study

Abstract: CD4+CD25+ Forkhead‑box protein 3 (Foxp3+) regulatory T cells are important in oral lichen planus (OLP). The present study aimed to investigate Foxp3 expression in CD4+CD25+ T cells of peripheral blood mononuclear cells and oral lesions in patients diagnosed with OLP, who were grouped as OLP subtype, duration and relapse. Using quantitative polymerase chain reaction (qPCR), western blotting and immunohistochemistry, Foxp3 expression levels in explants of oral lesions and CD4+CD25+ T cells from 32 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
0
14
0
2
Order By: Relevance
“…15 CD4þCD25þ Foxp3þ regulatory T cells have been shown to be associated with OLP, 30,44,51 as has dysregulation of Th17 cells 45,51 and the presence of CD3-IL-17þ cells. 15 Furthermore, the disturbed balance between Foxp3þ cells and IL-17 cells in OLP suggests altered local immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…15 CD4þCD25þ Foxp3þ regulatory T cells have been shown to be associated with OLP, 30,44,51 as has dysregulation of Th17 cells 45,51 and the presence of CD3-IL-17þ cells. 15 Furthermore, the disturbed balance between Foxp3þ cells and IL-17 cells in OLP suggests altered local immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The literature has shown that the increase in the ratio of CD8 + cells to FoxP3 + cells is associated with the development of several autoimmune diseases (Mempel et al, ), including the case of OLP‐I. It should be emphasised that in the cases of OLP, there is also a correlation between clinical characteristics and immune phenotype of T lymphocytes as erosive lesions, whose clinical characteristics were more exacerbated and therapeutic control was difficult, showed an increase in the amount of CD8 + lymphocytes and a decrease in the amount of FoxP3 + lymphocytes (Lei et al, ; Lorenzini, Viviano, Chisci, Chisci, & Picciotti, ). As for OLP‐HCV, some researchers believe that the chronic infection by HCV can produce an even more exacerbated expression of CD8 + T cells, which explains the development of complex clinical courses compared to lichenoid lesions and OLP‐I (Mega, Jiang, & Takagi, ).…”
Section: Discussionmentioning
confidence: 99%
“…When the reaction is mild, there is stimulation of epithelial activity, resulting in striations or white plaques. More intense lymphocyte activity may result in ulceration or atrophy of the epithelium . As this study proposed to evaluate genes related to inflammation, the reticular and plaque clinical forms of the disease were grouped in the same pool.…”
Section: Discussionmentioning
confidence: 99%